Loneliness, Depression and Health Status of the Institutionalized Elderly in Korea and Japan - Oksoo Kim, RN, PhD; Young-Soon Byeon, RN, PhD; Jung-Hee Kim, RN, PhD; Emiko Endo, RN, PhD; Makoto Akahoshi, RN, PhD; Hiromi Ogasawara, RN, MS (Elsevier, 2009)
The purpose of the study was to describe loneliness, depression, and health status in Korean and Japanese institutionalized elderly and explore differences between the countries. Also this study determined predictors of depression in each group. Methods: Elderly subjects, aged 65-98 (n = 184), were recruited from private nursing homes in Korea and Japan. Subjects were interviewed on health status, loneliness, and depression. Results: Korean subjects had higher loneliness scores than Japanese. More Korean elderly had depressive symptoms than Japanese elderly. The mean GDS score of Korean elderly was 8.07 and that of Japanese elderly was 5.21. Korean elderly had less physical function, and perceived their general health to be poor. Loneliness and perception of general health were significant predictors of depression in Korean and Japanese subjects. Conclusion: It is necessary to assess the levels of loneliness and depression of institutionalized Korean elderly and pursue an intervention to reduce these problems.